Perilaku Petani Miskin Dalam Mewujudkan Ketahanan Pangan Rumah Tangga di Lahan Sawah dan Lahan Kering Daerah Istimewa Yogyakarta - , S. DJUNI PRIHATIN, DRS.,M.SI. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This dissertation research aims to examine the behavior of poor farmers in achieving food security of households in the Yogyakarta Special Region, which is influenced by human capital factors, socio-cultural environment, the economy and the role of government agencies directly or indirectly. This type of research is an explanation with a survey method. The population studied was the recipient of poor rice farmers with a sample of 250 respondents, the sampling is done with the technique of simple random. Analysis was using path analysis. The research results obtained show that : 1. There are differences in the behavior of poor farmers in achieving food security of households in both lowland and upland. 2. Results of path analysis showed that the factors influencing the behavior of poor farmers in achieving food security of households, directly in lowland is variable attitudes, motivations, values, access to the village unit cooperatives, farmer groups and the role of village officials have accounted for 50 , 1%, the rest is influenced by other factors outside the model was 40.9%. 3. Results of path analysis showed that the factors influencing the behavior of poor farmers in achieving food security of households live in upland is variable motivation, selfefficacy, social interaction, farmer groups, barns and the role of agricultural extension has a contribution of 39.8% , the rest is influenced by factors outside the model was 60.2%. 4. The factors influencing the behavior of poor farmers in achieving food security of households in lowland, are attitudes, motivations, values, role of village officials, access to village cooperatives and farmer groups. While those affecting the behavior of farmers in achieving food security of poor households in the upland is motivation, selfconfidence, social interaction, the role of agricultural extension, barns and farmer groups. Keywords : farmer behavior, motivation, farmer groups, lowland, upland.